Preparation and Spectroscopic Studies of Some Metal Ion Complexes of 2-((4-Formyl-3-Hydroxynaphthalen-2-yl) Diazenyl) Benzoic Acid (Baghdad Science Journal, 2016)
New azo ligand 2-((4-formyl-3-hydroxynaphthalen-2-yl) diazenyl) benzoic acid (H2L) was synthesized from the reaction of 2-aminobenzoic acid and2-hydroxy-1-naphthaldehyde. Monomeric complexes of this ligand, of general formulae [MII(L)(H2O)] with (MII = Mn, Co, Ni, Cu, Zn, Pd, Cd and Hg ) were reported. The compounds were isolated and characterized in solid state by using 1H-NMR, FT-IR, UV–Vis and mass spectral studies, elemental microanalysis, metal content, magnetic moment measurements, molar conductance and chloride containing. These studies revealed tetrahedral geometries for all complexes except PdII complex is Square planar. The study of complexes formation via molar ratio of (M:L) as (1:1). Theoretical treatments of compounds in gas phase were studied using Hyper Chem-8 program has.